2013
DOI: 10.1002/oby.20323
|View full text |Cite
|
Sign up to set email alerts
|

In vivo precision of the GE iDXA for the assessment of total body composition and fat distribution in severely obese patients

Abstract: Objective: To evaluate the precision of the iDXA for total body composition and fat distribution measurements in severely obese patients. Design and Methods: Sixty-five severely obese participants with a mean age of 46 6 11years, BMI of 49 6 6 kg/m 2 , and a mean body mass of 137.3 6 20.9 kg took part in this investigation. Two consecutive iDXA scans with repositioning of the total body were conducted for each participant. The coefficient of variation (CV), the root-mean-square (RMS) averages of standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 7 publications
4
21
1
Order By: Relevance
“…[6] The Intraclass correlation coefficient (ICC) provided the measure of technique variance. [7] The correlation coefficient between iDXA and Prodigy of all body composition measurements (BM, FM, LTM, BMC, bone area, and BMD) are also reported. Linear regression was used to determine relationships between iDXA and Prodigy, and the method of Bland and Altman [8] was used to assess agreement between the two instruments.…”
Section: Methodsmentioning
confidence: 99%
“…[6] The Intraclass correlation coefficient (ICC) provided the measure of technique variance. [7] The correlation coefficient between iDXA and Prodigy of all body composition measurements (BM, FM, LTM, BMC, bone area, and BMD) are also reported. Linear regression was used to determine relationships between iDXA and Prodigy, and the method of Bland and Altman [8] was used to assess agreement between the two instruments.…”
Section: Methodsmentioning
confidence: 99%
“…To date, abdominal computed tomography (CT) and magnetic resonance imaging (MRI) have been the only direct measures of VAT ; despite being the current “gold standard” reference techniques to determine VAT, these approaches to measure VAT are expensive and time intensive, and CT imaging is associated with a high level of radiation exposure. A recent FDA‐approved software upgrade for DXA imaging has been validated against CT ( R 2 = 0.957) to measure visceral fat by determining abdominal fat from the android region and then calculating the differentiated compartments of SAT and VAT mass and volume . This method is fully automated, inexpensive, and readily available.…”
Section: Introductionmentioning
confidence: 99%
“…Precision error should be reported for both RMS SD and %CV though, highlighted by Carver and co-workers whose study in obese subjects reported similar %CV values (LM 1.0% and FM 0.9%), with reported RMS SD values at a factor of three higher than the studies cited above (22).…”
Section: Discussionmentioning
confidence: 80%